Impactos da graduação na qualidade de vida de universitários de educação física: um estudo de coorte - Costa, Andressa Moura (2021)
Introduction: Introduction: Quality of Life is the individual's perception of themselves, their cultural context and value system in which they live and in relation to their goals, expectations, standards and concerns. However, a large number of university students do not evaluate what can be considered a good quality of life during graduation. The objective of the study was to analyze the impact of graduation on the Quality of Life of university students from a Physical Education course and their sociodemographic associations. Method: Observational, cross-sectional analytical study with a quantitative approach, with university students from a Physical Education course in Goiás, Brazil. Data collection took place in the years 2015 and 2019, respective 1st and 8th periods. For data collection, a sociodemographic form and the WHOQOL-bref instrument were used. Results 26 physical education students participated in the study, with an average age of 18.6 ± 6.95 years, of which 61.53% were female (n = 16). The Environment domain obtained the lowest scores in 2015 and 2019 (2015 = 56.25 ± 10.23; 2019 = 56.61 ± 21.62). At the beginning of the course, the male gender showed significant differences for the Physical domain (78.21 ± 8.81 / p = 0.03) and General QOL index (77.45 ± 17.76 / p = 0.01) in relation to the male sex. In the comparison between the initial and final stages, there was a decline in the Physical domain score (2015 = 72.25 ± 11.48; 2019 = 67.85 ± 17.17) (p <0.02). Conclusion: The analysis of the Quality of Life of the university students brought worrying answers in the Environment domain of the WHOQOL-bref, both in 2015 and in 2019. Regarding training, there was no difference in 2019 between genders, however, male entrants, in 2015, presented better scores in the Physical domain and in the General QOL than females. In the evaluation between the beginning and the end of graduation, a worsening in the Physical domain was identified when the two stages of the research were compared.